Intraoral Laser Welding (ILW) in Implant Prosthetic Dentistry: Case Report - Carlo Fornaini; Elisabetta Merigo; Igor Cernavin; Gonzalo Lòpez de Castro; Paolo Vescovi (Hindawi Limited, 2012)
The aim of this clinical study was to describe the possibility of using the Nd:YAG laser device utilized in the dental offices to weld metals intraorally. The authors, before applying this technique "in vivo" on human subjects, tested the "in vitro" metal welding efficacy of dental Nd:YAG device firstly by interferometry, SEM, and EDS and subsequently by thermal camera and thermocouples in order to record temperature changes during the welding process on bovine jaws. Four implants were inserted in the edentulous maxillary arch of a 67 years old male patient. Immediately after that, a bar previously made by the dental technician was intraorally welded to the abutments by Nd:YAG laser (Fidelis Plus III, Fotona, Slovenia) with these parameters: 9.90 mJ, 1 Hz, 15 msec, 0.6 mm spot. Then the prosthesis was connected to the bar with four OT Caps. This clinical study, even if preliminary, suggests that laser welding technique may be intraorally used without side effects.